2022
DOI: 10.1021/acsami.2c06546
|View full text |Cite
|
Sign up to set email alerts
|

Codelivery of π–π Stacked Dual Anticancer Drugs Based on Aloe-Derived Nanovesicles for Breast Cancer Therapy

Abstract: To overcome the low efficacy of conventional monotherapeutic approaches that use a single drug, functional nanocarriers loaded with an amalgamation of anticancer drugs have been promising in cancer therapy. Herein, aloe-derived nanovesicles (gADNVs) are modified with an active integrin-targeted peptide (Arg-Gly-Asp, RGD) by the postinsertion technique to deliver indocyanine green (ICG) and doxorubicin (DOX) for efficient breast cancer therapy. We presented for the first time that the π−π stacking interaction c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“… 14 , 58 , 87 For example, Zeng et al used vesicles extracted from Aloe vera to encapsulate both the photosensitizer indocyanine green (ICG) and the small molecule chemotherapeutic agent doxorubicin (DOX), and this delivery system combined with phototherapy and chemotherapy showed effective inhibition of breast cancer cells. 88 Del Pozo-Acebo et al isolated EVs from broccoli, loaded them with exogenous miRNAs with biological effector capabilities, and then co-incubated them with Caco-2 cells. The results showed that the miRNA was taken up by this intestinal cell line and produced cytotoxicity, indicating that broccoli EVs have the potential to improve the biostability of therapeutic RNA and resist RNase degradation and gastrointestinal digestion.…”
Section: Engineering Of Pdvsmentioning
confidence: 99%
“… 14 , 58 , 87 For example, Zeng et al used vesicles extracted from Aloe vera to encapsulate both the photosensitizer indocyanine green (ICG) and the small molecule chemotherapeutic agent doxorubicin (DOX), and this delivery system combined with phototherapy and chemotherapy showed effective inhibition of breast cancer cells. 88 Del Pozo-Acebo et al isolated EVs from broccoli, loaded them with exogenous miRNAs with biological effector capabilities, and then co-incubated them with Caco-2 cells. The results showed that the miRNA was taken up by this intestinal cell line and produced cytotoxicity, indicating that broccoli EVs have the potential to improve the biostability of therapeutic RNA and resist RNase degradation and gastrointestinal digestion.…”
Section: Engineering Of Pdvsmentioning
confidence: 99%
“… [ 85 ] Aleo Target and Loading Indocyanine green and DOX ICG and DOX were premixed and incubated with NVs in PBS for 30 min at 37 °C, then pre-dissolved DSPE-PEG-RGD (using a 2:1 mixture of PBS and methanol) was added and incubated for 30 min, and the solution was centrifuged at 100000 g for 40 min. [ 95 ] Broccoli Loading miRNA The solution containing miRNAs was diluted with siRNA 1× buffer and incubated with Lipo2000 reagent at room temperature for 15 min. The filtered NVs was then incubated with the resulting mixture for 30 min at room temperature and kept at 4°C.…”
Section: Optimizating: Engineered Pdnvs As Drug Delivery Platform To ...mentioning
confidence: 99%
“… 85 When multiple drugs are loaded, there may be a “competitive” relationship between the drugs, and Zeng et al proposed using π-π stacking interactions to turn DOX and ICG into “friends”, making the relationship “cooperative” and improving drug delivery efficiency. 95 However, loading of large molecules remains the bottleneck, and techniques such as electroporation may damage the membrane structure of PDNVs. Further studies are needed to resolve the impact of recipient cell type, drug delivery method, molecular weight size, source of plant cells, loading co-incubation time, and drug solubility on loading efficiency.…”
Section: Optimizating: Engineered Pdnvs As Drug Delivery Platform To ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Zeng et al ( Zeng et al, 2022 ) argue that to overcome the drawbacks of traditional treatment methods, a functional nanocarrier loaded with mixed anticancer drugs has favourable prospects in breast cancer treatment. They found that aloe vera gel-derived nanovesicles (gADNV) is an example of an excellent nanocarrier in this regard.…”
Section: Application Of Plant-derived Extracellular Vesicles As the N...mentioning
confidence: 99%